Bacterial viability and antibiotic susceptibility testing with SYTOX green nucleic acid stain. - Roth, B L (1997)
A fluorescent nucleic acid stain that does not penetrate living cells was used to assess the integrity of the plasma membranes of bacteria. SYTOX Green nucleic acid stain is an unsymmetrical cyanine dye with three positive charges that is completely excluded from live eukaryotic and prokaryotic cells. Binding of SYTOX Green stain to nucleic acids resulted in a > 500-fold enhancement in fluorescence emission (absorption and emission maxima at 502 and 523 nm, respectively), rendering bacteria with compromised plasma membranes brightly green fluorescent. SYTOX Green stain is readily excited by the 488-nm line of the argon ion laser. The fluorescence signal from membrane-compromised bacteria labeled with SYTOX Green stain was typically > 10-fold brighter than that from intact organisms. Bacterial suspensions labeled with SYTOX Green stain emitted green fluorescence in proportion to the fraction of permeabilized cells in the population, which was quantified by microscopy, fluorometry, or flow cytometry. Flow cytometric and fluorometric approaches were used to quantify the effect of beta-lactam antibiotics on the cell membrane integrity of Escherichia coli. Detection and discrimination of live and permeabilized cells labeled with SYTOX Green stain by flow cytometry were markedly improved over those by propidium iodide-based tests. These studies showed that bacterial labeling with SYTOX Green stain is an effective alternative to conventional methods for measuring bacterial viability and antibiotic susceptibility.